1981
DOI: 10.1002/jpln.19811440509
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Binding Mechanism of Polysaccharide Cleaving Soil Enzymes by Clay Minerals

Abstract: Analyses of the sorption of five polysaccharide cleaving soil enzymes by Na‐homoionic clay minerals revealed a dependency on the cation exchange capacity of the clays: montmorillonite displayed the highest sorbing capacity, followed by palygorskite and kaolinite. Variation of the experimental conditions using cellulase and montmorillonite showed a maximum sorption at pH 4.8 and temperatures between 25°C and 45°C. Urea had no effect on the sorption, whereas humic acids and acetylation of enzymes lead to a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…For the phyllosilicates, montmorillonite adsorbed more of both enzymes than kaolinite, but with the larger effect for amylase than cellulase ( Figure 1 ). This is in line with previous studies on the adsorption of extracellular enzymes on pure minerals with montmorillonite retaining more enzyme than kaolinite [ 28 , 29 , 30 ] and goethite with higher sorption for β-glucosidase than montmorillonite [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…For the phyllosilicates, montmorillonite adsorbed more of both enzymes than kaolinite, but with the larger effect for amylase than cellulase ( Figure 1 ). This is in line with previous studies on the adsorption of extracellular enzymes on pure minerals with montmorillonite retaining more enzyme than kaolinite [ 28 , 29 , 30 ] and goethite with higher sorption for β-glucosidase than montmorillonite [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Hamzehi and Pflug [19] showed that the sorption of polysaccharases (i.e., cellulases, amyloglucosidase, pectinase, and α-amylase) was highest at their IEP when the enzymes had no net charge. Therefore they suggested that sorption takes place through van der Waals type forces.…”
Section: Sorption and Immobilizationmentioning
confidence: 99%
“…Proteins are strongly adsorbed to clay surfaces, reaching a maximum at their isoelectric point. This maximum has been variously interpreted as being due to electrostatic forces ( Norde & Lyklema, 1978), van der Waals forces ( Hamzehi & Pflug, 1981) and more recently as both electrostatic and hydrophobic interactions ( Quiquampoix & Ratcliffe, 1992; Staunton & Quiquampoix, 1994; Quiquampoix et al . 1995 ).…”
Section: Introductionmentioning
confidence: 99%